Sunni And Shia Communities’ Transformations In Lebanon: Changes In The Balance Of Power - Harutyunyan, Lilit (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The paper focuses on the transformations going on in Sunni and Shia communities in Lebanon within the framework of the current changes in the regional balance of power. The analysis of the transformations of the mentioned communities in Lebanon and of their impact on the internal and external levels provides one of the most relevant examples of the "sectarianization" of the Middle East, especially after 2011, which was also characterized by the struggle between Sunnis and Shiites. The confessional contradictions are deeply rooted in Lebanon, based on its confessional political system, but, despite the public rhetoric, both communities tend to have more pragmatic and accommodating attitudes instead of deepening confessional confrontations. While it is true that each community has witnessed the radicalization of certain positions and that, especially after 2011, major changes are taking place, which have been fuelled by the narrative that is mostly emerging at the regional level. Have regional developments influenced the national Lebanese ones? Has confessionalism been used as a tool of realpolitik in Lebanon? These are the main questions that are going to be examined.
Keywords: Confessional system; Balance of Power